Economic history of modern India - "Mishra, Girish" (New Delhi, 1998)
Encouraged by the welcome accorded to this book by readers, a new edition is being brought out. Though the basic structure remains unaltered, some new materials, especially in the chapter on famines, have been incorporated . A number of silly mistakes and printing errors that had crept into the earlier edition have been removed.
Keywords: India - Economic history